PEMODELAN INTEGRASI NEARLY REAL TIME DATA WAREHOUSE DENGAN SERVICE ORIENTED ARCHITECTURE UNTUK MENUNJANG SISTEM INFORMASI RETAIL - Sulastra, I Made Dwi Jendra; Sudarma, Made; Kumara, I Nyoman Satya (Majalah Ilmiah Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi Elektro, 2015)
Updates the data in the data warehouse is not traditionally done every transaction. Retail information systems require the latest data and can be accessed from anywhere for business analysis needs. Therefore, in this study will be made data warehouse model that is able to produce the information near real time, and can be accessed from anywhere by end users application. Modeling design integration of nearly real time data warehouse (NRTDWH) with a service oriented architecture (SOA) to support the retail information system is done in two stages. In the first stage will be designed modeling NRTDWH using Change Data Capture (CDC) based Transaction Log. In the second stage will be designed modeling NRTDWH integration with SOA-based web service. Tests conducted by a simulation test applications. Test applications used retail information systems, web-based web service client, desktop, and mobile. Results of this study were (1) ETL-based CDC captures changes to the source table and then store it in the database NRTDWH with the help of a scheduler; (2) Middleware web service makes 6 service based on data contained in the database NRTDWH, and each of these services accessible and implemented by the web service client.
Keywords: Nearly realtime data warehouse; service oriented architecture; change data capture; transaction log; web service